Metropolitan Kallistos of Diokleia as historian of the Eastern Orthodox Church - Moschos, Dēmētrios N. (International journal for the study of the Christian church, 2019)
Metropolitan Kallistos of Diokleia treats the history of the Eastern Orthodox Church not as a mere academic account of separate events, but rather as a means of manifesting the self-understanding of being Orthodox in unbreakable continuity with the Early Church. He seeks also to present this identification in language suitable to an audience living in the modern West. In this task he outlines the historical background of important theological or canonical aspects of the life of the Orthodox Church (e.g. ministry, synodality etc.) in his publications and the more important critical moments of the relations between East and West, especially the so-called rebaptism controversy' in the second half of the eighteenth century. In so doing, he manages to state the distinct position of Eastern Orthodoxy without taking a polemical or biased position.